Biografie - Lebenslauf - Generation Perspektiven der Erwachsenenbildung - Dörner, Olaf; Iller, Carola; Pätzold, Henning; Franz, Julia; Schmidt-Hertha, Bernhard (Schriftenreihe der Sektion Erwachsenenbildung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2017)
People interpret their biographies in order to give them a subjective meaning. In institutionalized biographies, biographies also become normatively charged patterns of progress. They reflect the tension between life courses and culturally and socially shaped generalized patterns of life-style. The volume collects selected peer-reviewed contributions on this topic.